Mammographic Image Contrast Enhancement Through The Use Of Moving Contrast Sweep. - Mohd Nordin, Zailani; Mat Isa, Nor Ashidi; Ngah, Umi Kalthum; Zamli, Kamal Zuhairi (2008)

(untitled)
Low contrast in mamographic image has always made detection of subtle signs such as the presence of micro calcification within dense tissue a challenge.